Susceptibility of Rhipicephalus (Boophilus) microplus to ivermectin (200, 500 and 630 mu g/kg) in field studies in Brazil - Cruz, Breno Cayeiro [UNESP] (2015)
The present study aimed to determine the susceptibility of 17 Rhipicephalus (Boophilus) microplus populations, originating in the Southeast and Southern regions of Brazil, to different ivermectin concentrations (200, 500 and 630 mu g/kg), administered through subcutaneous or topical (pour-on) routes. R. (B.) microplus populations from the states of Minas Gerais (seven populations), Sao Paulo (seven populations) and Parana (three populations) were chosen for the tests. The selected cattle were allocated to treatment groups on day 0, and block formation was based on the arithmetic mean of female ticks (4.5-8.0 mm long) counted on three consecutive days (-3, -2 and -1). To evaluate the therapeutic and residual efficacies of these formulations, tick counts (females ranging from 4.5 to 8.0 mm long) were performed on days 3,7 and 14 post-treatment, and continued on a weekly basis thereafter until the end of each experiment. The results obtained throughout this study, utilizing field efficacy studies, allowed us to conclude that the resistance of R. (B.) microplus against 200 and 500 mu g/kg ivermectin is widely disseminated because all tick populations that had contact with these specific concentrations were diagnosed as resistant. However, it is possible to infer that R. (B.) microplus resistance against 630 mu g/kg ivermectin was also widespread, diagnosed at six of ten analyzed properties. Resistance of these ectoparasites to 630 mu g/kg ivermectin is most likely emerging in three other populations of R. (B.) microplus. Strategies of resistance management need to be quickly determined to keep the selection pressure at a minimum level in Brazil. (C) 2014 Elsevier B.V. All rights reserved.